Annexin A7 Levels Increase in Rats With Traumatic Brain Injury and Promote Secondary Brain Injury - Gao, Fan; Li, Di; Rui, Qin; Ni, Haibo; Liu, Huixiang; Jiang, Feng; Tao, Li; Gao, Rong; Dang, Baoqi (Frontiers in Neuroscience, 2018)
The incidence of traumatic brain injury (TBI) has been increasing annually. Annexin A7 is a calcium-dependent phospholipid binding protein. It can promote melting of the cell membrane. Recent studies have shown that it plays an important role in atherosclerosis, other cardiovascular diseases, and a variety of tumors. However, few studies of ANXA7 in TBI have been performed. We here observed how ANXA7 changes after TBI and discuss whether brain injury is associated with the use of ANXA7 antagonist intervention. Experimental Results: 1. After TBI, ANXA7 levels were higher than in the sham group, peaking 24 h after TBI. 2. The use of siA7 was found to reduce the expression of A7 in the injured brain tissue, and also brain edema, BBB damage, cell death, and apoptosis relative to the sham group. Conclusion: ANXA7 promotes the development of secondary brain injury (SBI) after TBI.